Clinical Profile of Adult Organophosphorus Compound Poisoning in a Tertiary Care Hospital - Hoq, Md Enamul; Islam, AKM Shafiqul; Sharmin, Rubaba; Akbar, Mohammad Shafiqullah; Islam, Mohammad Mushaidul; Roy, Soumitra; Fayaz, Md Abul (Central Medical College Journal, 2022)
Despite the apparent benefits of organophosphate compounds (OPCs) acute organophosphate (OP) pesticide poisoning is an increasing problem worldwide. In a country like Bangladesh, where agriculture is a major component of the economy, these compounds are readily available to the general public. There is paucity of evidence from Bangladesh showing the pattern of organophosphate poisoning (OPP) in healthcare facilities. The aim of this study is to see the clinical profile of organophosphorus compound poisoning in admitted patients of tertiary care hospital. Methods: This observational cross-sectional study was carried out over all admitted patient with OPC poisoning in the department of Medicine, Cumilla Medical college, Cumilla from July 2019 to January 2020. A total of 100 cases were enrolled in the study. Patients having history of poisoning with OPC compound were stabilized by ABC care system and then assessed according to detailed history, physical examination and paradeniya organophosphorus poisoning (POP) scale. Results: The mean age was found 25.0±8.0 years and male to female ratio was 1:1.2, were mostly married (78.0%) and most of them from poor family (86%). The commonest manner of poisoning was suicidal (90.0%) with oral ingestion. More than eighty (84.0%) percent patients came from rural area. Commonest symptoms were abdominal pain (88.0%), vomiting (63.0%), excessive sweating (58.0%), salivation (35.0%), breathlessness (34.0%) and lacrimation (27.0%). Total hospitalization period was more than one week and less than two weeks in majority of cases (73%) and mortality rate was 2.0%. Conclusion: Due to increasing numbers of organophosphorus poisoning cases in younger age groups strict legislature on the availability of organophosphate compounds, preventive measures and appropriate health education should be introduced to decrease the incidence. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 76-83